Modern blast furnace ironmaking [2nd. ed.] an introduction - Geerdes, Maarten; Toxopeus, Hisko; Vliet, Cor van der (Amsterdam IOS Press, 2009)
Describes the principles of the blast furnace process and especially the control of the process. This book focuses on the control of the blast furnace process with respect to thermal control, gas flow control and casthouse operation. It is suitable for students of metallurgy as well as for blast furnace operators and management.
Keywords: Blast furnace